Kontribusi Program Pekarangan Pangan Lestari (P2L) terhadap Upaya Percepatan Penurunan Stunting di Kabupaten Sleman: Analisis Masa Pandemi COVID-19: Kontribusi Program Pekarangan Pangan Lestari (P2L) terhadap Upaya Percepatan Penurunan Stunting di Kabupaten Sleman selama Masa Pandemi Covid-19 - Renita, Renita; Helmyati, Siti; Purwaningrum, Digna Niken; Sitorus, Nova Lidia; Dilantika, Charisma (Amerta Nutrition, 2023)
Background: There are disparities in the level of household food security achievements between regions and getting worse with Covid-19 pandemic which has also inhibited nutritional improvement acceleration. The P2L is one of the priority programs in maintaining community food security. However, the implementation of this program is still vulnerable to sustainability. Objectives: This study aims to examine the contribution of P2L during Covid-19 pandemic in maintaining community food and nutrition security and its role to accelerate stunting reduction in Sleman Regency. Methods: This research was a descriptive qualitative with case study approach. Sample selection used a purposive maximum variation sampling method for parties actively involved in the P2L. Data collection methods were carried out using in-depth interviews, closed question types questionnaires, documentation, and participatory observation by directly involved in group activities. Results: The P2L acted as a living food barn that can provide food during Covid-19 pandemic. Vegetables were the main commodity that were able to fulfill household needs at 60% and 40% at the medium level. Meanwhile, other food commodities had not been developed optimally in the yard. However, the P2L not only had a positive impact on improving nutrition and the household economy of KWT members, but also for vulnerable communities in the surrounding area. To accelerate stunting reduction, the results from P2L were also used to support Integrated Healthcare Center activities such as providing PMT. Conclusions: The P2L program has a positive impact for the community, but it is necessary to innovate crop-livestock-fruit integration in each area and strengthen institutions in order to make the program sustainable.